Case Report: Narcolepsy patients masked behind obstructive sleep apnea syndrome (OSAS): report of 2 cases and literature review - Simin Zou; Xiaomei Zhang; Yinping Shen; Zhongxia Shen; Zhong Wang; Benhong Wang (Frontiers in Neuroscience)
Obstructive sleep apnea syndrome (OSAS) and narcolepsy are sleep disorders that commonly present with excessive daytime sleepiness (EDS). OSAS is characterized by recurrent upper airway obstruction during sleep, leading to intermittent hypoxia and sleep fragmentation. Narcolepsy is a chronic sleep-wake disorder characterized by EDS, cataplexy, vivid hallucinations, and sleep paralysis. The overlap of symptoms can lead to misdiagnosis and delayed appropriate treatment. We report two male patients who initially presented with symptoms suggestive of OSAS, including loud snoring, witnessed apneas, and significant daytime sleepiness. Despite appropriate OSAS management with continuous positive airway pressure (CPAP), both patients continued to experience EDS and reported episodes of cataplexy, sleep paralysis, and vivid dreams. Polysomnography (PSG) confirmed mild to moderate OSAS, and multiple sleep latency tests (MSLT) revealed mean sleep latencies of less than 5 min with multiple sleep-onset REM periods (SOREMPs). Based on the presence of cataplexy and MSLT findings, narcolepsy type 1 (NT1) was diagnosed in both cases. Treatment with modafinil in conjunction with CPAP therapy led to significant improvement in symptoms and quality of life. These cases highlight the importance of considering narcolepsy in patients with persistent EDS despite adequate OSAS treatment. Coexistence of NT1 and OSAS can obscure the diagnosis of narcolepsy, leading to delays in appropriate management. Comprehensive evaluation, including detailed patient history and sleep studies, is crucial. Combined therapy targeting both conditions may be effective in managing symptoms and improving patient outcomes.